Partitioning Control Mechanism and Engineering Practice of Rebuilding Bearing Arch in Surrounding Rock under High Ground Stress - Mengtang Xu; Ke Li; Youlin Xu (Advances in Civil Engineering)
The mining of coal seam has a significant influence on the stability of the roadway near it, especially under the condition of high ground stress. To study the control mechanism of the surrounding rock under the influence of high ground stress, a general idea for the partition control of the rebuilding bearing arch (RBA) was proposed in this paper. Based on the basic mechanical performance test of the bearing arch, this paper built a mechanical model of the RBA based on Protodyakonov’s pressure arch theory, analyzed the influence of the strength of the bearing arch on the surrounding rock failure, and obtained the ultimate thickness of the bearing arch failure under high ground stress. The results show that the RBA’s damage is closely related to the overburden load and RBA’s thickness. The tensile stress and shear stress of RBA increase linearly with the overburden load increase and increase sharply with the load-bearing arch’s thickness, showing a nonlinear relationship. To maintain the surrounding rock’s stability, it is necessary to ensure that the RBA’s thickness is within a specific range. The results are applied to the Wantian coal mine. The theoretically determined load-bearing thickness is 10 m, which can effectively control the surrounding rock deformation and significantly reduce the roadway’s repair rate.